Security systems’ status with the use of technical means of video recording and video surveillance: international experience, perspectives for implementation in the activities of the National police of Ukraine (Law and Safety, 2020)
Search for criminals becomes more difficult in modern conditions of continuous growth of the population of big urban centers and more and more frequent use of the latest achievements of science and technology by criminals for the realization of their purposes and for counteraction to law enforcement agencies. To increase the efficiency of the search for offenders it is necessary to introduce the latest technologies. Therefore, the systems of video recording and video surveillance, which currently operate in Ukraine and are one of the areas of using these technologies, have been studied. It has been noted that the installed CCTV cameras mostly work in manual mode. The employee of the information processing center must watch the video in order to gather evidence and search for suspects. It takes a lot of time and requires the involvement of a large number of staff, which makes the search for criminals and obtaining evidence from video surveillance systems ineffective.Tendencies in the development of intelligent video surveillance systems in developed countries have been analyzed. It has been found out that such countries (EU, USA, China, Russia) install modern “smart” CCTV cameras, the information from which is sent to modern situational centers, where it is processed by using artificial intelligence, neural networks and cloud infrastructure. Certain types of cameras even have the ability to independently process the received information. This makes it possible to perform biometric facial recognition, to detect behavioral abnormalities of suspects who intend to commit offenses; to record the appearance and disappearance of objects, to recognize the state car plates, to recognize their type, brand and color, to record the way of their movement, to carry out the analysis of these factors on the basis of these factors to search for suspects and cars in the city.Video surveillance centers, in particular within one of the most important areas of public safety – traffic safety – have the ability to recognize prohibited or atypical traffic, to capture the intersection of the restricted area or the intersection of the visual line, to respond to the passage of people in a given direction, to identify traffic conditions, to detect traffic density, congestion and mass congestion of vehicles, to respond to the appearance of people in the surveillance zone, etc.Based on the review of the experience of introduction and use of video surveillance systems in Ukraine and analysis of their development in developed countries, the authors have suggested the ways to modernize and further develop security systems in Ukraine by using CCTV cameras.
Keywords: security; video recording; video surveillance; artificial intelligence